LOYALITAS DAN KEPUASAN PELANGGAN DITENTUKAN OLEH KETERSEDIAAN FASILITAS USAHA DAN HARGA - Alyanti, Futrie; Khusaini; Jamalus (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2025)
Research aim : This study aims to analyze the effect of facilities and prices on customer satisfaction and loyalty of Rumah Kedua Coffee & Space. Design/Methode/Approach : The researcher used a quantitative research method with a cross-sectional survey technique. The researcher used an infinite population. The sample size was 400 respondents (incidental sampling, sampling error = 5%). Distribution and collection of data through online questionnaires via WhatsApp. Research Finding : The results Price has a stronger influence in increasing customer satisfaction, compared to increasing loyalty. While facilities increase loyalty more than customer satisfaction. Furthermore, control variables such as brand image, service quality, and product quality also contribute significantly to customer satisfaction and loyalty. Theoretical contribution/Originality : This study proves that in increasing customer satisfaction and loyalty of coffee in Tangerang Municipality requires different treatments. Competitive pricing is more able to increase satisfaction, while the availability of facilities increases customer loyalty of coffee in Tangerang Municipality. These results enrich the theory of customer satisfaction and loyalty. Practitioner/Policy implication : The results of this study provide real contributions to the coffee shop industry, especially for Rumah Kedua Coffee & Space in developing pricing strategies to increase customer satisfaction and loyalty. This study provides new insights into the provision of adequate facilities so that it can increase customer loyalty, especially in the cafe industry in the Tangerang Municipality area. Research limitation : The study is limited to one location in Tangerang Municipality. In addition, the researcher has ignored important variables, namely relative advantage, service dominant logic, culture, location, and taste.